No fault divorce in Caribbean juridisctions : style over substance - Walker, Joseph A. (2013)
Examines the divorce regimes - the fault, mixed fault, no fault and the Antigua and Barbuda model within the Caribbean, resulting from legislative reforms, to evaluate the proposition that these reforms are more form than substance and as such have not achieved their stated or implied objectives.